If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 3x = 4x + -7 Reorder the terms: 5 + 3x = -7 + 4x Solving 5 + 3x = -7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + 3x + -4x = -7 + 4x + -4x Combine like terms: 3x + -4x = -1x 5 + -1x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + -1x = -7 + 0 5 + -1x = -7 Add '-5' to each side of the equation. 5 + -5 + -1x = -7 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = -7 + -5 -1x = -7 + -5 Combine like terms: -7 + -5 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| cos29=17.3/x | | 45=x+(x-2)+(x-4) | | -14-(-20)=x/4 | | 237760+26x=3000000 | | C=(2a-3b)/2 | | x+2(4x-1)+18=42 | | (6x+1)=(4x-11) | | http://media.education2020.com/evresources/4072-01-02-05-00_files/i0250000.jpg | | 2m^2-14m=0 | | (5n)=(32+n) | | 2x/3-3x/4=12 | | 6/11=18/k-5 | | 29x-11+15x=45 | | 2x+5=56+5 | | 6/11=18/k-11 | | 3/5=p/10 | | 0=6x^2+60x-7200 | | sin^-1(-(sqrt(2)/2)) | | 5/3=p/10 | | 8c-(-3)+(-c)=-4 | | 2(5-9x)=-3(x-2) | | 3/p=60 | | 6x+18=4x^2+x^2 | | 3^1/3c=80 | | (4c-6)/(3c)=2 | | (7x-6)(x^2-7x+1)= | | 250x-500=10000 | | (6m-12)=0 | | 5c-10-3c=-4 | | 1.8k+0.9k= | | 3c-12-(-3c)=c+8 | | 9x-4=9x-1 |